Smart IoT-based temperature-controlled cooling system for solar panels using Arduino - Mula Sreenivasa Reddy; Kondragunta Rama Krishnaiah; Anjali Devi Gorla; Anantha Sravanthi Peddinti; Sanam Nagendram; Mohammad Najumunnisa; Bodapati Venkata Rajanna; Shaik Hasane Ahammad; Gongati Pandu Ranga Reddy (International Journal of Applied Power Engineering (IJAPE), 2026)
The efficiency of solar photovoltaic panels declines significantly as their surface temperature increases beyond optimal levels. This paper presents a smart, temperature-controlled cooling system based on an Arduino UNO microcontroller to enhance solar panel performance by mitigating overheating. The system integrates a DS18B20 temperature sensor and a moisture sensor to monitor real-time environmental conditions. When the temperature exceeds a defined threshold, the Arduino activates a CPU fan and water pump to dissipate heat effectively. Experimental testing demonstrated an efficiency improvement of approximately 10% to 12% during peak solar conditions. A hysteresis logic-based system with autonomous control is used to control the amount of energy and water utilized, by only cooling when required. An LCD screen displays real-time information locally on-site, while an ESP8266 WiFi module sends information to a "cloud" so that remote monitoring can occur through the ThingSpeak cloud service. The entire system operates entirely from solar energy and is capable of being operated off-the-grid as well as being environmentally friendly. Due to its low cost, modularity, and energy efficiency, this smart cooling solution provides a viable solution for rural areas or areas with limited resources to enhance the performance of photovoltaic systems.